A critical analysis of Purnomo and colleagues" interpretation in Matthew 6:9–13 - Laia, Harman Z. (HTS teologiese studies, 2025)
The reinterpretation of the Lord’s Prayer (Mt 6:9–13) as a prayer of thanksgiving rather than petition, based on their argument that the aorist tense in imperative and/or subjunctive verbs signifies actions completed in the past, along with their critique of the Lembaga Alkitab Indonesia (LAI) translation as erroneous, sparked debates among Christians in Indonesia and was leveraged by non-Christian groups to question the Bible’s authenticity. This study aimed to evaluate the validity of Purnomo et al.’s research by focussing on their interpretation of the aorist tense in imperative and/or subjunctive verbs, research methodology, use of literature, critique of the LAI translation and theological implications. A comprehensive review of literature and exegesis was conducted to analyse the grammatical, linguistic, methodological and theological aspects of the text. Based on a detailed examination, this study found that their interpretation of the aorist tense in imperative and/or subjunctive verbs in the prayer was unsupported by linguistic evidence and contradicted the principles of biblical Greek grammar, where the aorist tense emphasises ‘aspect’ rather than ‘time’ (e.g., ‘past tense’) of actions. Consequently, the theology derived from their study was flawed. Moreover, the study affirmed that the LAI translation accurately reflects the original context of the text. This research concluded that Purnomo et al.’s interpretation of the Lord’s Prayer (Mt 6:9–13) contained significant theological and linguistic errors that require revision.Contribution: This research critically contributes to biblical theology by addressing interpretative challenges in Matthew 6:9–13, refuting claims that the Lord’s Prayer expresses gratitude based on the aorist tense. It reaffirms the prayer as a supplication, grounded in biblical Greek grammar and theology, while defending the accuracy of the LAI translation. Advancing critical exegesis, the study promotes rigorous theological discourse and a deeper understanding of Scripture.